2018
DOI: 10.4254/wjh.v10.i7.452
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary role of liver biopsy in hepatocellular carcinoma

Abstract: A correct diagnosis of hepatocellular carcinoma (HCC) in cirrhotic patients with focal liver lesions is one of the most important issues nowadays. Probably one of the oldest debates in the hepatology community is whether to perform liver biopsy (LB) in all cirrhotic patients with focal liver lesions. We now face a time when oncology is moving towards personalized medicine. According to the current European Association for the study of Liver diseases HCC guidelines, LB has only a minor role in the management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 74 publications
2
27
0
Order By: Relevance
“…The rate of biopsy success, which was defined as providing sufficient amount of tissue for histopathologic confirmation of malignant lesion, was 93.4% in our study (93.6% in liver biopsies [US-guided], 89.7% in lung biopsies [CT-guided]). This figure is comparable or higher than those of previous studies on liver [11,12] and lung biopsies [1316]. Various studies have investigated the factors affecting biopsy success rate, and reported that selecting appropriate target lesion is one of the most important steps for a successful biopsy [8,17].…”
Section: Discussionsupporting
confidence: 71%
“…The rate of biopsy success, which was defined as providing sufficient amount of tissue for histopathologic confirmation of malignant lesion, was 93.4% in our study (93.6% in liver biopsies [US-guided], 89.7% in lung biopsies [CT-guided]). This figure is comparable or higher than those of previous studies on liver [11,12] and lung biopsies [1316]. Various studies have investigated the factors affecting biopsy success rate, and reported that selecting appropriate target lesion is one of the most important steps for a successful biopsy [8,17].…”
Section: Discussionsupporting
confidence: 71%
“…The indications for tissue biopsy in HCC have evolved over time [7]. The development of high-throughput technologies has allowed the detection of molecular drivers of tumorigenesis and of specific DNA mutations in tumor biopsy samples, which may be able to predict response or resistance to targeted therapies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of HCC relies on a number of different diagnostic methods, including ultrasound, computed tomography, biopsy and blood tests ( 2 ). Liver biopsy is regarded as the ‘gold standard’ for the diagnosis of HCC; however, liver biopsies are invasive procedures where the patient often experiences complications, such as bacteremia or death (risk of death, ~0.01%) ( 3 ). Similarly, there are certain disadvantages to ultrasound and computed tomography, which limit their effectiveness in the diagnosis.…”
Section: Introductionmentioning
confidence: 99%